High fever or hypotension predicts non‐hypoglycemia in patients with impaired consciousness in prehospital settings. Issue 1 (1st March 2021) - Mizu, Daisuke; Matsuoka, Yoshinori; Huh, Ji‐Young; Ariyoshi, Koichi
Abstract : Aim: To evaluate whether vital signs can predict whether hypoglycemia can be eliminated as the cause of impaired consciousness in prehospital settings. Methods: We extracted the data of patients who underwent blood glucose measurements by paramedics in Kobe City, Japan from April 2015 to March 2019. We used receiver operating characteristic curves and calculated the area under the curve (AUC) to evaluate the validity of the vital signs in distinguishing hypoglycemia. We also calculated stratum‐specific likelihood ratios to examine the threshold at which hypoglycemia becomes less likely for each vital sign. Results: Of the 1, 791 patients, 1, 242 were eligible for analysis. Hypoglycemia was observed in 324 patients (26.1%). Significant differences in each vital sign were noted between the hypoglycemic and non‐hypoglycemic groups. Body temperature was moderately accurate in differentiating between the two groups (AUC, 0.71; 95% confidence interval, 0.68–0.74). Furthermore, in patients with systolic blood pressure <100 mmHg and body temperature ≥38°C, it was unlikely that hypoglycemia caused impaired consciousness (stratum‐specific likelihood ratios 0.12 and 0.15; 95% confidence intervals, 0.05–0.25 and 0.06–0.35, respectively). Conclusion: In the prehospital assessment of patients with impaired consciousness, high fever or hypotension was helpful in differentiating between hypoglycemia and non‐hypoglycemia. In particular, body temperature ≥38°C or systolic blood pressure <100 mmHg indicated a low likelihood of hypoglycemia. A validation study is needed to confirm the findings in this study. Abstract : Body temperature was moderately accurate in differentiating hypoglycemia and non‐hypoglycemia in the prehospital setting. If there is a high temperature or hypotension, it is less likely that hypoglycemia is the cause of impaired consciousness.